PSIKOLOGI KEPRIBADIAN DALAM PERSPEKTIF ISLAM - Zaini Zaini (CV. ADIBA ASIHA AMIRA, 2022)
Psychology is a psychological problem so that if it is associated with Islam, it has a long vision and mission which is not only a psychological problem but also concerns the soul in the context of Islam. The research conducted is a literature review where the results of this study find; First, psychology can be interpreted as a science that studies the mental relationship with behavioral steps, especially relating to the environment. Second, the literal understanding of personality contains at least four meanings, namely; Mentality, Personality, Individuality, and Identity. Third, personality can be interpreted as a typical way of reacting from an individual to social stimuli and the quality of his adjustment to the social aspect of his environment. Fourth, broadly speaking, the type of human personality is divided into three aspects, namely; Biological, Sociological and Psychological aspects